Medical device regulation (MDR) from a dental perspective - Dirk Mohn; Matthias Zehnder (Frontiers Media S.A., 2023)
A new regulation for the marketing and application of medical devices has become applicable in the European Union as of May 2021. This regulation is termed EU 2017/745 or Medical Device Regulation (MDR). Initially published and entered into force in 2017, it replaces the former Medical Device Directive 93/42/EEC (MDD), but is still under amendment. The implication of this legislation have broad effects on manufacturers, importers, distributors, users of medical devices, and patients. This article discusses the MDR from the dental perspective. As is illuminated in this text, the MDR will create more red tape for industrial players to get their products CE (Conformitée Européenne) marked, and more documentation work for dentists. This also means that smaller companies acting out of Europe are affected in a disproportionally negative manner compared to their globally acting counterparts. The MDR could and most probably will result in a considerable reduction and price increase of the products that are available to European dentists. Moreover, the MDR could create a rift between dental materials scientists working at universities and the dental industry, because the latter now has to direct more money towards regulatory affairs rather than product development or innovation. On the other hand, the MDR may also act as an antetype for similar regulations in other parts of the world, and could offer new career opportunities for individuals in dental materials research, especially in the regulatory field.